Path to Increasing p-B11 Reactivity via ps and ns Lasers. (24th December 2022) - Mehlhorn, Thomas A.; Labun, Lance; Hegelich, Bjorn Manuel; Margarone, Daniele; Gu, Ming Feng; Batani, Dimitri; Campbell, E. Michael; Hu, S. X.
Abstract : The Lawson criterion for proton-boron (p- 11 B) thermonuclear fusion is substantially higher than that for deuterium-tritium (DT) because the fusion cross section is lower and peaks at higher ion energies. The Maxwellian averaged p- 11 B reactivity peaks at several hundred keV, where bremsstrahlung radiation emission may dominate over fusion reactions if electrons and ions are in thermal equilibrium and the losses are unrestricted. Nonequilibrium burn has often been suggested to realize the benefits of this aneutronic reaction, but the predominance of elastic scattering over fusion reactivity makes this difficult to achieve. The development of ultrashort pulse lasers (USPL) has opened new possibilities for initiating nonequilibrium thermonuclear burns and significant numbers of p- 11 B alpha particles have been reported from several experiments. We present an analysis that shows that these significant alpha yields are the result of beam fusion reactions that do not scale to net energy gain. We further find that the yields can be explained by experimental parameters and recently updated cross sections such that a postulated avalanche mechanism is not required. We use this analysis to understand the underlying physics of USPL-driven nonequilibrium fusion reactions and whether they can be used to initiate fusion burns. We conclude by outlining a path to increasing the p- 11 B reactivity towards the goal of achieving ignition and describing the design principles that we will use to develop a computational point design.